2000
DOI: 10.1068/a3265
|View full text |Cite
|
Sign up to set email alerts
|

Call Centre Growth and Location: Corporate Strategy and the Spatial Division of Labour

Abstract: The authors contribute to the developing literature on call centres by providing detailed empirical evidence on the spatial unevenness in the distribution of call centre activity. They argue that the driving forces of call centre growth, whether as the rationalisation of back-office functions or as entirely new entities, have been corporate strategy and the pursuit of low-cost competitive advantage. Thus, although technological developments at the heart of call centre operations render them relatively ‘footloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 13 publications
4
45
0
1
Order By: Relevance
“…A comparison of the results with the previous work of Bristow et al (2000) also reveals a number of similarities. In particular, both studies conclude that population density and a lagged measure of employment in financial and business services have a positive impact on call centre location.…”
Section: Empirical Analysis Of the Determinants Of The Location Of Casupporting
confidence: 64%
“…A comparison of the results with the previous work of Bristow et al (2000) also reveals a number of similarities. In particular, both studies conclude that population density and a lagged measure of employment in financial and business services have a positive impact on call centre location.…”
Section: Empirical Analysis Of the Determinants Of The Location Of Casupporting
confidence: 64%
“…It is certainly the case that dependence on the public sector means that areas are vulnerable to reductions in government expenditure (Marshall et al, 1999). Public sector call centres, an important source of new jobs in peripheral areas in recent years (Bristow et al, 2000), are like their private sector counterparts in principle vulnerable to transfer overseas. To date there have been few moves abroad, though call centres contracted to the private sector to manage could ultimately result in the transfer of activity offshore.…”
Section: Negative Impacts Of Relocation On Origin and Destination Areasmentioning
confidence: 99%
“…Research on UK peripheral regions confirms that call centres have until fairly recently provided a significant source of employment growth at least over the past ten years (BRISTOW, MUNDAY and GRIPAIOS 2000;BISHOP GRIPAIOS andBRISTOW 2003, DEPARTMENT OF TRADE AND INDUSTRY 2004). Despite the potential for locational dispersal throughout the urban hierarchy, however, studies have shown that call centres tend to be highly concentrated in larger urban centres.…”
Section: Introductionmentioning
confidence: 86%
“…In the UK, the impacts of these changes on the development of cities and regions has been widely researched including studies of locational determinants and their impacts on employment (BRISTOW, MUNDAY and GRIPAIOS 2000;BISHOP, GRIPAIOS andBRISTOW 2003, RICHARDSON, BELT andMARSHALL, 2000;RICHARDSON and BELT, 2001). Early expansion of call centres focussed primarily on finance and insurance industries (MARSHALL and RICHARDSON, 1996), but the approach was soon adopted widely across many sectors including prominently in travel and transport, computer services, distribution, hotels, telecommunications retailing and utilities.…”
Section: Introductionmentioning
confidence: 99%